(untitled) (Orfeu, 2023)
Autism consists of a severe neurodevelopmental disorder that can present outstanding features in reciprocal social communication and social interaction. According to studies, sensorineural disorder is present in approximately 95% of children with autism. The present work is a case study that seeks to present the understanding of the musical development of a five-year-old boy, male, diagnosed with autism, level one and with signs of sensory alterations. Data were collected from the application of the DEMUCA scale added to the observations made during music classes. We expect that the data can contribute with possible strategies that support the development of musical activities with an extension of profund observation at the ambience and the individuality of each child. Futhermore, to motivate discussions and reflections on inclusion and its relationship with the practice developed from knowledge about the differences and specificities of students with spectrum disorder in music classes.